Protect, profit, profess, promote: Establishing legitimacy through logics of diversity in Canadian accounting firm recruitment documents. (13th July 2016) - Bujaki, Merridee; Durocher, Sylvain; Brouard, François; Neilson, Leighann; Pyper, Rhonda
Abstract: Prospective accounting recruits are increasingly diverse. Drawing on a theoretical framework that combines legitimacy theory, impression management, and institutional logics, we use content analysis to examine how the eight largest Canadian accounting firms refer to diversity in their recruitment websites. Our analysis reveals accounting firms adopt multiple institutional logics and various impression management strategies to enhance legitimacy in the eyes of prospective diversity‐sensitive employees. We find four "Ps" of diversity‐related institutional logics—protect, profit, profess, and promote—all of which are at play in accounting firms' websites. Further, we find that diversity is far from being an institutionalized concept. Copyright © 2015 ASAC. Published by John Wiley & Sons, Ltd.